DISMANTLING THE POWER RELATIONS OF THE PRE-WEDDING PHOTO PHENOMENON IN BALANGAN BEACH - Dinata, Ramanda Dimas Surya; Wijaya, I Putu Sinar; Wijaya, Agung (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Photography is one of the forms of identity in visual images. Photographic work (pre wedding photo) is only one visual image that is produced as a form of breeding signs from the world of reality that can affect social relations, and forms of sociality since the last ten years. The problem that occurs is the practice of commercialization of natural space to religious exploitation on Balangan beach, Nusa Dua, Bali in the phenomenon of pre wedding photo. It is necessary to answer the form of power relations, ideology, and implications arising from the phenomenon of pre-wedding photo. The theory of knowledge power relations, Bourdieu's practice theory, and ideological theory are used to dismantle the power relations of knowledge that exist on Balangan beach. Qualitative methods are used as a method of collecting data, therefore we can know that land owners, heads of the environment, travel agents are the actors who capture that knowledge to influence, control, regulate the existence of the presence of commercialization and religious exploitation on Balangan beach. There is no denying the implications of increasing the economy, utilizing social capital, and building relationships causing the sustainability and continuation of the commercialization of Balangan beach as the object of pre-wedding photo shoots that will continue to be carried out over a long period of time.